Perception Is Reality: quality metrics in pancreas surgery – a Central Pancreas Consortium (CPC) analysis of 1399 patients. Issue 5 (May 2016) - Abbott, Daniel E.; Martin, Grace; Kooby, David A.; Merchant, Nipun B.; Squires, Malcolm H.; Maithel, Shishir K.; Weber, Sharon M.; Winslow, Emily R.; Cho, Clifford S.; Bentrem, David J.; Kim, Hong Jin; Scoggins, Charles R.; et al.
Abstract: Introduction: Several groups have defined pancreatic surgery quality metrics that identify centers delivering quality care. Although these metrics are perceived to be associated with good outcomes, their relationship with actual outcomes has not been established. Methods: A national cadre of pancreatic surgeons was surveyed regarding perceived quality metrics, which were evaluated against the Central Pancreas Consortium (CPC) database to determine actual performance and relationships with long-term outcomes. Results: The most important metrics were perceived to be participation in clinical trials, appropriate clinical staging, perioperative mortality, and documentation of receipt of adjuvant therapy. Subsequent analysis of 1399 patients in the CPC dataset demonstrated that a R0 retroperitoneal and neck margin was obtained in 79% (n = 1109) and 91.4% (n = 1278) of cases, respectively. 74% of patients (n = 1041) had >10 lymph nodes harvested, and LN positivity was 65% (n = 903). 76% (n = 960) of eligible patients (surgery first approach) received adjuvant therapy within 60 days of surgery. Multivariate analysis demonstrated margin status, identification of >10 lymph nodes, nodal status, tumor grade and delivery of adjuvant therapy within 60 days to be associated with improved overall survival. Conclusions: These analyses demonstrate that systematic monitoring of surgeons' perceived quality metrics provides critical prognostic information, which is associated with patient survival.